THE AMOUNT OF PLASTID PIGMENTS IN THE LEAVES OF SOY VARIETIES - MAMUROV HURSHIDJON ABDUVOKHIDOVICH; Toshkenboeva Munira Erkinjan Kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article presents the results of experimental work on the amount of plastid pigments in the leaves of soy varieties.